2006
DOI: 10.1063/1.2204334
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and magnetic structures and their temperature dependence of Co2Z-type hexaferrite (Ba,Sr)3Co2Fe24O41 by high-temperature neutron diffraction

Abstract: We have prepared nonoriented and magnetically oriented specimens of Co2Z-type Ba ferrite Ba3Co2Fe24O41 (Ba3Z) and those with Sr2+ substitution for Ba2+, i.e., Ba1.5Sr1.5Co2Fe24O41 (Ba1.5Sr1.5Z) and Sr3Co2Fe24O41 (Sr3Z) with the conventional solid-state reaction method. Permeability measurements of nonoriented specimens have shown that this substitution improves the frequency characteristic of permeability, though the permeability in Sr3Z significantly decreases. X-ray diffraction (XRD) and magnetization measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…This is in agreement with the known literature; up to now, in the structural studies of Z-hexaferrite (Ba x Sr 1−x ) 3 Co 2 Fe 24 O 41 , no polar space group was resolved 23,24 and the electric polarization P ⊥ z was observed only in an external magnetic field. 3,8 Nevertheless, for final proving or disproving of the polar crystal structure, we propose further complementary experiments, such as second-harmonic generation or high-resolution electron diffraction.…”
Section: Raman Scatteringsupporting
confidence: 79%
“…This is in agreement with the known literature; up to now, in the structural studies of Z-hexaferrite (Ba x Sr 1−x ) 3 Co 2 Fe 24 O 41 , no polar space group was resolved 23,24 and the electric polarization P ⊥ z was observed only in an external magnetic field. 3,8 Nevertheless, for final proving or disproving of the polar crystal structure, we propose further complementary experiments, such as second-harmonic generation or high-resolution electron diffraction.…”
Section: Raman Scatteringsupporting
confidence: 79%
“…This also resulted in the magnetic moment of the cobalt ions being quenched between 200-250°C in Sr 3 Co 2 Z, 50-100°C lower than the other Co 2 Z ferrites. Takada et al also observed the two-step magnetisation loop first reported by Pullar and Bhattacharya, and noted that in oriented polycrystalline samples this effect [68] was much more pronounced when the applied field was measured along the easy direction (c-axis) [94]. Such features were not seen in the Sr 1.5 Ba 1.5 Co 2 Z magnetisation loops.…”
Section: Z Ferritesmentioning
confidence: 68%
“…However, in oriented polycrystalline Sr 3 Co 2 Z the easy axis of MCA was in a cone at an angle of 52.3°to the c-axis at RT, [94] and remained so up to 200°C, before rapidly decreasing further to *25°at only 250°C, and moving fully to the c-axis at the same temperature as the other Co 2 Z ferrites [68]-so it is uniaxial at room temperature, despite being a very soft ferrite. From neutron diffraction data, the ions filling the ten different possible Wyckoff positions for iron and cobalt ions were obtained by Takada et al This demonstrated that, while in Sr 1.5 Ba 1.5 Co 2 Z cobalt occupies six sites (Me1(2a), Me2(4f), Me4(12 k), Me5(4e), Me8(12 k) and Me10(2d)), in Sr 3 Co 2 Z cobalt only occupies the first four of these [68]. This means that Co 2+ is not present in the Me8(12 k) or Me10(2d) positions-in other words, it is not present at all in the R block of Sr 3 Co 2 Z, unlike in other Co 2 Z ferrites (Fig.…”
Section: Z Ferritesmentioning
confidence: 93%
See 2 more Smart Citations